2023
DOI: 10.3390/pharmacy11010039
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Intercultural Development Inventory (IDI) to Assess Intercultural Competence at U.S. Pharmacy Schools

Abstract: Background: U.S. pharmacy schools need to engage in improving intercultural competence among administrators, faculty, staff, and students. The Intercultural Development Inventory (IDI) can be a possible tool to determine the level of intercultural competence. U.S. pharmacy schools need to examine the validity of the IDI within the context of health professional education prior to using this tool. Objectives: To describe the relationship between the IDI and its underlying theory, identify whether the validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Notably, the IDI recommends 30-50 hours of intentional engagement in the selfreflective process to shift DOs. 38 e number of hours that each student dedicated to cultural competence development across the DPTprogram curriculum is unknown but was likely significantly less than that recommended by the IDI. e change in cultural competence and accuracy of self-perception of cultural competence during year 1 suggests that students may have naturally engaged in more self-reflection and increased selfawareness as they transitioned into a new phase of life through the pursuit of their educational and career goals within a professional DPT education program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the IDI recommends 30-50 hours of intentional engagement in the selfreflective process to shift DOs. 38 e number of hours that each student dedicated to cultural competence development across the DPTprogram curriculum is unknown but was likely significantly less than that recommended by the IDI. e change in cultural competence and accuracy of self-perception of cultural competence during year 1 suggests that students may have naturally engaged in more self-reflection and increased selfawareness as they transitioned into a new phase of life through the pursuit of their educational and career goals within a professional DPT education program.…”
Section: Discussionmentioning
confidence: 99%
“…Based on normally distributed IDI results in the general population, approximately 65.25% of people, on average, have Minimization as their primary orientation. 38 A study 35 investigating the cultural competence of students, faculty, and staff within a College of Nursing in the midwestern United States found that most participants scored within the Minimization orientation on the IDI preintervention, consistent with the general population. Similarly, a study 23 conducted in Australia found that pre-and post-mean IDI scores of physical, occupational, and speech therapy students who participated in international clinical placements began and remained within the Minimization orientation.…”
Section: Minimization Orientationmentioning
confidence: 92%
See 2 more Smart Citations
“…Chiu & Shi, 2019;Deardorff, 2006), however, noted that while different descriptors for the definitions are available, there seems to be little conceptual difference, at least at the broad definitional level, across these concepts. For example, in Hammer (2013), intercultural competence is defined as "the capability to shift cultural perspective and appropriately adapt behavior to cultural difference and commonalities" (p. 26). In Deardorff (2006), cross-cultural competence is defined as the "ability to communicate effectively and appropriately in intercultural situations based on one's intercultural knowledge, skills and attitudes" (pp.…”
mentioning
confidence: 99%